Parametric study on tank integration for hydrogen civil aviation propulsion - Huete, Jon; Pilidis, Pericles (Elsevier, 2021)
Hydrogen powered gas turbine propulsion will play a central role in the decarbonisation of civil aviation. A key challenge is the integration of large liquid hydrogen tanks into the aircraft, given the low density of liquid hydrogen. Hydrogen offers a quarter of the energy content, per unit volume and one third of the fuel weight, when compared to a conventional fuel. Optimising tank weight is seen as key to aircraft usefulness. A detailed evaluation of tanks for civil aviation is presented here, covering a very wide range of sizes and design solutions. For passenger air transport, if the choice is made not to vent, dormancy time (the time the tank can be allowed to operate without vapour or important fuel extraction) becomes a key design parameter. This paper highlights the interdependence of Maximum Allowable Operating Pressure and the amount of insulation with heating and venting, considering the influence of dormancy time. The resulting tank gravimetric efficiency is presented for cylindrical tanks with hemispheric ends (a very likely choice for tank design). Notwithstanding conservative analysis, tank gravimetric efficiencies of 65–70% can be achieved. This permits combined fuel and tank weights that are less than half of those of current aircraft. The issue that then becomes critical is the resulting large tank and aircraft volume.
Keywords: Hydrogen; PropulsionTank; Long-range; Aircraft